2020
DOI: 10.1186/s13023-019-1274-3
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between GLA variants and alpha-Galactosidase A profile in dried blood spot: an observational study in Brazilian patients

Abstract: Background: Fabry disease is a rare X-linked inherited disorder caused by deficiency of α-Galactosidase A. Hundreds of mutations and non-coding haplotypes in the GLA gene have been described; however, many are variants of unknown significance, prompting doubts about the diagnosis and treatment. The α-Galactosidase A enzymatic activity in dried blood spot (DBS) samples are widely used for screening purposes; however, even when values below the normal are found, new tests are required to confirm the diagnosis. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
2
10
0
2
Order By: Relevance
“…A previous study suggests that sequencing of the GLA gene is the most useful method for screening for FD, however, they do not detect any patient with the disease. 34 Our results confirm this statement, because in all patients with pathogenic variants the disease was confirmed. Regarding enzyme activity or accumulation of substrate in DBS, the measurement of α-Gal A activity is a better screening method to identify patients with FD in both males and females.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…A previous study suggests that sequencing of the GLA gene is the most useful method for screening for FD, however, they do not detect any patient with the disease. 34 Our results confirm this statement, because in all patients with pathogenic variants the disease was confirmed. Regarding enzyme activity or accumulation of substrate in DBS, the measurement of α-Gal A activity is a better screening method to identify patients with FD in both males and females.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were obtained by Varela et al, where they showed a mean enzyme activity in males with pathogenic variants of 0.27 μmol/L/h, much lower than that obtained in men without variants (1.77 μmol/L/h). 34 All the diagnosed patients presented low levels of enzyme activity, but not all showed elevation of lyso-Gb3. Two of the 10 diagnosed males did not present accumulation of lyso-Gb3 (patients #12 and #21), both with a late-onset phenotype and 50 and 72 years old respectively.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Although valuable tools to improve diagnosis and identify undiagnosed patients, screening studies for Fabry disease, may reveal individuals with GLA variants of yet unknown significance or non-pathogenic (likely) benign variants (Doheny et al, 2018;Germain, Fouilhoux, et al, 2019;Germain & Jurca-Simina, 2018;Germain et al, 2020;van der Tol et al, 2014;Varela et al, 2020). Reanalysis of the GLA variants identified in 63 previously published screening studies demonstrated that 47.9% of males and 74.1% of females had non-pathogenic variants (Doheny et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Dried blood spot (DBS) technology that can be stored stably enables new possibilities for bioanalytical procedures that can be beneficial for patients, health care providers, and laboratories, and the technology can be inexpensive (8). The sampling can be performed in a non-hospital environment and is suitable for large-scale disease screening (9). DBS technology also reduces the sample processing burden and is characterized by straightforward waste disposal.…”
Section: Introductionmentioning
confidence: 99%